Impact Analysis Of Madrasah Climate On Its Productivity In West Bandung Regency - Putri, Eliza Metiasari (Universitas Pendidikan Indonesia, 2017)
Abstractâ The background of this study focuses on the influence of madrasah aliyah climate on its productivity in West Bandung regency. The purpose of the study is to illustrate: 1) madrasah climate in West Bandung regency 2) the influence of Madrasah Climate on the productivity of madrasah aliyah in West Bandung regency. The research method is using descriptive method with questionnaire collecting technique toward 187 certified teachers spread in madrasah that have accreditation A and B. The description of research result indicates that Madrasah Climate is in good category or quite high and the madrasah climate has a positive effect on its productivity.KeywordsâImpact Analysis, Madrasah Climate, Madrasah Productivity